The Effect Of Physical Work Environment And Work Discipline On Employee Performance At The Youth And Sports Agency Of North Sumatera Province - Fatmasari Fatmasari; Hasrul Azwar Hasibuan; Muhammad Yalzamul Insan (Journal of Management, Economic, and Accounting, 2026)
This study was carried out to investigate how physical work environment variable along with work discipline variable impact civil servant achievement at Youth and Sports Agency of North Sumatra Province. Quantitative methodology featuring causal associative pattern was applied. A total of 83 Civil Servants were designated as both population and sample using the saturated sample method. Data collection was conducted using a five-point Likert-scaled questionnaires, then processed using multiple linear regression analysis with IBM SPSS application version 25. Research findings show that physical work environment variable have a positive and significant impact on civil servant performance, shown by t-value 3.168 with significance 0.002 (< 0.05). the work discipline variable also showed a positive and significant impact with t-value 6.433 and significance 0.000 (< 0.05). Simultaneously, both variables have a positive and significant on civil servant performance with F-value 103.858 and significance 0.000 (< 0.05). Determination coefficient (R²) figure of 0.722 demonstrates that 72.2% of civil servant performance variation can be explained by physical work environment variable and work discipline variable, while remaining portion is influenced by factors outside research framework.